Comparative analysis between 1-D, 2-D and 3-D carotid web quantification. (16th February 2022) - Perry da Camara, Catarina; Nogueira, Raul G; Al-Bayati, Alhamza R; Pisani, Leonardo; Mohammaden, Mahmoud; Allen, Jason W; Nahab, Fadi; Olive Gadea, Marta; Frankel, Michael R; Haussen, Diogo C
Abstract : Background: Carotid webs (CaW) are now recognized as a cause of ischemic stroke in young patients. The thromboembolic potential appears related to the CaW's morphology and consequent impact on local flow dynamics. We aim to evaluate the reliability of different measurement methods for the quantification of CaW and their relationship to symptomatic status, presence of large vessel occlusion stroke (LVOS), clot burden and final infarct volume. Methods: This was a retrospective analysis of the local comprehensive stroke center CaW database (September 2014–July 2019). CT angiograms (CTAs) were reviewed independently by two raters, blinded to the clinical information and laterality of the stroke/transient ischemic attack. CaW were quantified with 1-D (length), 2-D (area) and 3-D (volume) measurements via Osirix software. Final infarct volume was calculated on MRI. Patients with superimposed CaW thrombus and no repeat imaging were excluded. Results: Forty-eight CaW (37 symptomatic and 11 contralateral/asymptomatic) in 38 patients were included. Mean age (±SD) was 48.7 (±8.5) years, 78.9% were women and 77.1% were black. Inter-rater agreement was 0.921 (p<0.001) for 1-D, 0.930 (p<0.001) for 2-D, and 0.937 (p<0.001) for 3-D CaW measurements. When comparing symptomatic with asymptomatic CaW, mean web length was 3.2 mm versus 2.5 mm (p<0.02), median area was 5.8 versus 5.0 mm 2 (p=0.35) and median volume was 15.0 versus 10.6 mm 3 (p<0.04), respectively. CaW with a thinner profile (longer intraluminal projection compared with the base) were more likely to be symptomatic (0.67±0.17 vs 0.88±0.37; p=0.01). Average CaW 1-D and final infarct volume had a weak but positive association (Κ=0.230, p<0.05), while no association among web measurements and the presence of LVOS or clot burden was observed. Conclusion: CaW dimension quantification (1-D, 2-D and 3-D) is highly reproducible. Linear and volumetric measurements were more strongly associated with symptoms. The impact of CaW size on the presence of LVOS, clot burden and final infarct volume is unclear.